2018
DOI: 10.1002/cche.10118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xanthan gum on dough properties and bread qualities made from whole wheat flour

Abstract: Background and objectives This study aimed to determine the effect of xanthan gum on whole wheat dough and bread, especially dough rheological properties, gluten structures, loaf volume, and bread texture and staling. Findings Xanthan gum increased the water absorption and mixing time for whole wheat dough as determined by mixograph. Xanthan gum altered dough rheology as evaluated through the Kieffer extensibility test, Chen–Hoseney stickiness test, and compression test employed for extensional viscosity calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
1
22
1
1
Order By: Relevance
“…Similarly, Tebben and Li (2019) found that increasing the concentration of gums in bread samples could increase the specific volume of bread. However, Joel et al.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Tebben and Li (2019) found that increasing the concentration of gums in bread samples could increase the specific volume of bread. However, Joel et al.…”
Section: Resultsmentioning
confidence: 88%
“…It made bread yellower ( p < .05), but no significant difference was observed between other bread samples. Tebben and Li (2019) showed that the addition of xanthan gum did not have a significant effect on the lightness of whole wheat bread, but adding high levels of this gum led to a significant increase in a * and b * of samples. Hosseini‐Esfehani and Fadavi (2019) reported that incorporating tragacanth and guar hydrocolloids to the bread formulation reduced the lightness of bread, which attributed this decrease in lightness to an increase in the Millard browning reaction in the presence of gums.…”
Section: Resultsmentioning
confidence: 99%
“…The texture profiles of the bread crumb were measured, using a TA-XT Plus Texture Analyzer (Stable Micro Systems, Surrey, U.K.) following a previous method [27]. Three slices from each treatment were measured on days 1, 4, and 7, respectively.…”
Section: Bread Quality Analysismentioning
confidence: 99%
“…However, the higher hydration of the doughs and the water‐retention capacity of the hydrocolloids can generate more humid breads, compensating for the typical dryness of WG products (Heiniö et al., 2016). In a recent study, Tebben and Li (2019) analyzed the ability of xanthan gum to improve the quality of gluten‐free bread. They agree with previous studies on the need to increase water absorption and dough development times, but they achieve a clear increase in the volume of the breads and a reduction in hardness.…”
Section: How To Improve the Quality Of Whole‐grain Wheat Flours And Wmentioning
confidence: 99%